On the low-cycle fatigue response of CoCrNiFeMn high entropy alloy with ultra-fine grain structure. (15th February 2021) - Picak, S.; Wegener, T.; Sajadifar, S.V.; Sobrero, C.; Richter, J.; Kim, H.; Niendorf, T.; Karaman, I.
Abstract: High Entropy Alloys (HEAs) are a new class of multi-component alloys with excellent tensile strength-ductility combination. Their yield strength levels, however, are still low as compared to other high strength materials. Here, Equal Channel Angular Pressing (ECAP) was employed to improve the yield strength of the most well-known HEA, CoCrFeMnNi, through microstructural refinement. The cyclic response of both coarse and ultrafine grained CoCrFeMnNi was investigated during strain-controlled low cycle fatigue tests under fully reversed push-pull loading at room temperature. The microstructural evolution during cyclic loading was compared to the microstructure under quasi-static monotonic loading. Very high yield strength levels around 1 GPa were obtained after ECAP. In addition, ECAP samples demonstrated a superior fatigue life at relatively low strain amplitudes while coarse grained samples exhibited a better fatigue life at the highest strain amplitude considered. X-ray diffraction, electron backscattered diffraction and transmission electron microscopy were performed to reveal underlying mechanisms for the superior fatigue life and the overall transient behavior upon cycling. The fatigue life and hardening behavior were governed by the refined grain size, high density dislocation walls, and the annihilation of existing dislocations resulting in the formation of cell structures in the ECAP samples. The lower fatigue life of the ECAP samples at the highest strain amplitude is attributed to the higher stress amplitudes and cyclic softening due to accelerated dislocation annihilation. Finally, the formation of dislocation cell structures and high-density dislocation walls simultaneously is rationalized by the effect of applied stress on the partial dislocation separation. Graphical abstract: Image, graphical abstract